Method for manufacturing a composite layer material and a radome

CN123001267APending Publication Date: 2026-10-30ZHUHAI GUONENG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611021136.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0002]传统的天线罩,具有以下结构特征,(1):采用全金属结构,此时存在重量重以及电磁屏蔽严重的问题;(2):采用全树脂结构,此时存在力学强度不足以导致易变形的问题;(3)采用树脂蒙皮和泡沫芯层复合的结构,树脂蒙皮和泡沫芯层复合时,两者之间通过树脂胶粘接,并且采用等压或者升压的方式配合恒温热压来压合层叠的蒙皮层和芯层,这种热压方式无法实现蒙皮层和芯层复合功能最优化

Benefits of technology

在本申请中,通过胶层、聚丙烯预浸带材层和聚甲基丙烯酰亚胺泡沫芯层的复配,以及搭配三段升温加热的热压方式,以及配合三段加热过程中的热压压力调控,使得热压得到的复合层材具有较好的抗弯曲性、抗冲击性以及较好的X波段透波率,另外,本申请得到的复合层材由聚合物复合得到,相比于金属材质,本申请的复合层材具有重量轻的优势,并且通过热压参数调控即可成型,因此还具有制备工艺简单的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123001267A_ABST
    Figure CN123001267A_ABST
Patent Text Reader

Abstract

This application provides a method for preparing a composite layer material and an antenna radome, comprising: forming a preform in which the adhesive layer comprises epoxy resin and nano-titanium dioxide, and a polypropylene prepreg tape layer is formed by laying glass fiber reinforced polypropylene prepreg tape, wherein the volume fraction of glass fiber is 45%-60%; hot pressing with a vacuum degree ≤-0.095MPa, raising the hot pressing temperature to 70-90℃ and holding it for 5-15min, further raising the hot pressing temperature to 110-130℃ and holding it for 15-25min, further raising the hot pressing temperature to 140-160℃ and holding it for 10-25min, wherein the hot pressing pressure is 0.9-1.0 MPa during the first stage of heating, 0.7-0.8 MPa during the second stage of heating, and 0.5-0.6 MPa during the third stage of heating; maintaining the hot pressing pressure during the third stage of heating, stopping heating, and allowing it to cool naturally to room temperature. The resulting composite material has good bending resistance, impact resistance, and X-band transmittance, and also has the advantage of being lightweight. The preparation method provided in this application has the advantage of simple preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of radome material preparation, specifically to a method for preparing a composite layer material and an radome. Background Technology

[0002] Traditional radomes have the following structural features: (1) They adopt an all-metal structure, which results in heavy weight and severe electromagnetic shielding problems; (2) They adopt an all-resin structure, which results in insufficient mechanical strength leading to easy deformation; (3) They adopt a composite structure of resin skin and foam core layer. When the resin skin and foam core layer are composited, they are bonded together by resin glue, and the layered skin and core layer are pressed together by constant pressure or pressure increase combined with constant temperature hot pressing. This hot pressing method cannot achieve the optimal composite function of the skin layer and core layer. (4) The skin layer and foam core layer perform different functions, so their material properties are very different. For example, one is polypropylene and the other is polymethacrylamide. Conventional resin glue is difficult to have good adhesion to both at the same time, which is not conducive to achieving better composite performance. Summary of the Invention

[0003] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for preparing a composite layer material. The resulting composite layer material has good bending resistance, impact resistance and good X-band transmittance, and also has the advantage of light weight. The preparation method provided by this application has the advantage of simple preparation process.

[0004] To solve the above problems, the technical solution adopted by the present invention is as follows: A method for preparing a composite layer material includes the following steps: In a hot press mold, a prepreg tape layer, an adhesive layer, a polymethacrylamide foam core layer, another adhesive layer, and a polymethacrylamide tape layer are formed sequentially from bottom to top to form a preform. The closed-cell rate of the polymethacrylamide foam core layer is greater than or equal to 95%. The adhesive layer comprises epoxy resin and nano-titanium dioxide, with the amount of nano-titanium dioxide being 0.5%-2% of the total weight of the adhesive layer components. The polymethacrylamide tape layer is formed by laying glass fiber reinforced polymethacrylamide tape, in which the volume fraction of glass fiber is 45%-60%. The pre-pressed body is hot-pressed with a vacuum degree ≤ -0.095MPa. A three-stage heating method is used: the first stage involves raising the hot-pressing temperature to 70-90℃ and holding it for 25-35 minutes; the second stage involves raising the hot-pressing temperature further to 110-130℃ and holding it for 55-65 minutes; and the third stage involves raising the hot-pressing temperature further to 140-160℃ and holding it for 110-125 minutes. During the first stage of heating, the hot-pressing pressure is 0.9-1.0 MPa; during the second stage, the hot-pressing pressure is 0.7-0.8 MPa; and during the third stage, the hot-pressing pressure is 0.5-0.6 MPa, resulting in the hot-pressed body. Maintain the hot-pressing pressure during the third stage of heating, then stop heating and allow the hot-pressed body to cool naturally to room temperature; Demolding yields the composite layer material.

[0005] In some possible implementations, during the second stage of heating, the hot-pressing temperature is further increased to 110-120°C.

[0006] In some possible embodiments, the adhesive layer further comprises polyether-modified organopolysiloxane, ethylene propylene non-conjugated diene terpolymer grafted with maleic anhydride, polypropylene grafted with maleic anhydride, and an organic solvent. The amount of polyether-modified organopolysiloxane is 0.5%-3% of the total weight of the adhesive layer components, the amount of ethylene propylene non-conjugated diene terpolymer grafted with maleic anhydride is 2%-5% of the total weight of the adhesive layer components, the amount of polypropylene grafted with maleic anhydride is 3%-7% of the total weight of the adhesive layer components, the amount of organic solvent is 5%-10% of the total weight of the adhesive layer components, and the balance is the epoxy resin.

[0007] In some possible embodiments, the epoxy resin is composed of silicone-modified epoxy resin and bisphenol A type epoxy resin, wherein the weight ratio of the silicone-modified epoxy resin to the bisphenol A type epoxy resin is 1:(35-45).

[0008] In some possible implementations, the weight ratio of the silicone-modified epoxy resin to the bisphenol A type epoxy resin is 1:(40-45).

[0009] In some possible implementations, the weight ratio of the ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride to the polypropylene grafted with maleic anhydride is 1:(1-1.5).

[0010] In some possible implementations, the heating rate is 5-6°C / min in the first stage of heating, 2-4°C / min in the second stage of heating, and 7-10°C / min in the third stage of heating.

[0011] In some possible implementations, the polypropylene prepreg tape layer has at least two stacked layers of polypropylene prepreg tape, each layer of polypropylene prepreg tape being laid in one of 0°, 90°, or ±45°, and the laying directions of the polypropylene prepreg tape in different layers are different.

[0012] In some possible implementations, before hot pressing, the thickness of the polypropylene prepreg tape layer is 0.3-0.6 mm, the thickness of the polymethacrylimide foam core layer is 10-15 mm, and the thickness of the adhesive layer is 0.1-0.3 mm.

[0013] This application also provides an antenna radome made of a composite material layer obtained by the preparation method described above.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: In this application, by combining an adhesive layer, a polypropylene prepreg tape layer, and a polymethacrylimide foam core layer, and by using a three-stage heating hot-pressing method, along with the control of the hot-pressing pressure during the three-stage heating process, the hot-pressed composite material has good bending resistance, impact resistance, and good X-band transmittance. In addition, the composite material obtained in this application is made of polymer composites, which has the advantage of being lightweight compared to metal materials, and can be formed by controlling the hot-pressing parameters, thus also having the advantage of a simple manufacturing process.

[0015] In addition, since the radome is made of composite material, it has both the mechanical properties and wave transmission properties of composite material.

[0016] The present invention will be further described in detail below with reference to the specific embodiments and accompanying drawings. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the stacking of the layers of the preparatory body provided in an embodiment of this application.

[0018] Figure 2 This is a schematic diagram of a structure in which two polypropylene prepreg tapes are laid in an overlapping manner at 0° and 90°.

[0019] Figure 3 This is a schematic diagram of a structure in which two polypropylene prepreg tapes are laid in an overlapping manner at ±45°.

[0020] Explanation of icon numbers: 20-Polypropylene prepreg tape layer; 21-Polypropylene prepreg tape; 30-Adhesive layer; 40-Polymethacrylimide foam core layer. Detailed Implementation

[0021] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0023] The following describes some embodiments of the present invention in detail. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0024] One embodiment of this application provides a method for preparing a composite layer material, comprising the following steps.

[0025] Reference Figure 1 Step 1: A pre-prepared body is formed sequentially from bottom to top within a hot-press mold, consisting of a polypropylene prepreg tape layer 20, an adhesive layer 30, a polymethacrylimide foam core layer 40, and another adhesive layer 30. Specifically, the pre-prepared body comprises the sequentially stacked polypropylene prepreg tape layer 20, adhesive layer 30, polymethacrylimide foam core layer 40, adhesive layer 30, and polypropylene prepreg tape layer 20. The closed-cell rate of the polymethacrylimide foam core layer 40 is greater than or equal to 95%. For example, the density of the polymethacrylimide foam core layer 40 can be 30-100 kg / m³. The adhesive layer 30 comprises epoxy resin and nano-titanium dioxide, with the amount of nano-titanium dioxide being 0.5%-2% of the total weight of the adhesive layer components. The polypropylene prepreg tape layer is formed by laying glass fiber reinforced polypropylene prepreg tape 21, in which the volume fraction of glass fiber in the polypropylene prepreg tape 21 is 40%-60%.

[0026] In some embodiments, the adhesive layer 30 further comprises a polyether-modified organopolysiloxane, an ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride, a polypropylene grafted with maleic anhydride, and an organic solvent. The amount of the polyether-modified organopolysiloxane is 0.5%-3% of the total weight of the adhesive layer components, the amount of the ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride is 2%-5% of the total weight of the adhesive layer components, the amount of the polypropylene grafted with maleic anhydride is 3%-7% of the total weight of the adhesive layer components, the amount of the organic solvent is 5%-10% of the total weight of the adhesive layer components, and the balance is epoxy resin. By further optimizing the composition of the adhesive layer 30, the mechanical properties of the composite layer can be further improved. For example, the organic solvent includes at least one of toluene and xylene.

[0027] In some embodiments, the epoxy resin is composed of silicone-modified epoxy resin and bisphenol A type epoxy resin, with a weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin of 1:(35-45). Preferably, the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:(40-45). Optimizing the proportion of different types of epoxy resins is beneficial to further improving the mechanical properties of the composite layer.

[0028] In some embodiments, the weight ratio of the ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride to the polypropylene grafted with maleic anhydride is 1:(1-1.5). Setting the ratio of grafted polymers is beneficial to further improve the mechanical properties of the composite layer.

[0029] In some embodiments, the polypropylene prepreg tape layer 20 has at least two stacked layers of polypropylene prepreg tape 21, and the laying direction of each layer of polypropylene prepreg tape 21 is one of 0°, 90°, and ±45°, and the laying directions of different layers of polypropylene prepreg tape 21 are different. For example, when the polypropylene prepreg tape layer 20 has two stacked layers of polypropylene prepreg tape 21, the layer furthest from the adhesive layer 30 is defined as the first layer. In this case, the first layer of polypropylene prepreg tape 21 can be laid at 0°, and the corresponding second layer can be laid at 90° (see reference). Figure 2 When the polypropylene prepreg tape layer 20 has three stacked polypropylene prepreg tapes 21, the first layer of polypropylene prepreg tape 21 can be laid at 0°, the second layer of polypropylene prepreg tape 21 can be laid at 90°, and the third layer of polypropylene prepreg tape 21 can be laid at either +45° or -45° (see reference). Figure 3 And so on. It is understandable that the laying arrangement of the polypropylene prepreg tape layers 20 on both sides of the core layer can be different. Increasing the number of polypropylene prepreg tape layers 21 can improve the mechanical properties of the composite material, but has little impact on wave transmittance.

[0030] In some embodiments, before hot pressing, the thickness of the polypropylene prepreg tape layer 20 is 0.3-0.6 mm, the thickness of the polymethacrylimide foam core layer 40 is 10-15 mm, and the thickness of the adhesive layer 30 is 0.1-0.3 mm. It is understood that the thicknesses of the polypropylene prepreg tape layers 20 on both sides of the core layer can be the same or different, and the thicknesses of the adhesive layers 30 on both sides of the core layer can also be the same or different.

[0031] Step 2: Hot pressing preparation. The vacuum degree for hot pressing is ≤-0.095MPa. A three-stage heating method is used for hot pressing. The first stage heating method is to raise the hot pressing temperature to 70-90℃ and hold it for 5-15 minutes. The second stage heating method is to continue raising the hot pressing temperature to 110-130℃ and hold it for 15-25 minutes. The third stage heating method is to continue raising the hot pressing temperature to 140-160℃ and hold it for 10-25 minutes. During the first stage heating, the hot pressing pressure is 0.9-1.0 MPa. During the second stage heating, the hot pressing pressure is 0.7-0.8 MPa. During the third stage heating, the hot pressing pressure is 0.5-0.6 MPa, thus obtaining the hot-pressed body.

[0032] In some embodiments, during the second stage of heating, the hot-pressing temperature is further increased to 110-120°C.

[0033] In some embodiments, preferably, the heating rate is 5-6°C / min during the first stage of heating, 2-4°C / min during the second stage of heating, and 7-10°C / min during the third stage of heating.

[0034] Step 3: Maintain the hot-pressing pressure during the third stage of heating, stop heating, and allow the hot-pressed body to cool naturally to room temperature.

[0035] Step 4: Demolding to obtain the composite layer material.

[0036] In this application, by combining the adhesive layer 30, the polypropylene prepreg tape layer 20, and the polymethacrylimide foam core layer 40, and by using a three-stage heating hot pressing method, along with the control of the hot pressing pressure during the three-stage heating process, the composite material obtained by hot pressing has good bending resistance, impact resistance, and good X-band transmittance. In addition, the composite material obtained in this application is made of polymer composite, which has the advantage of being lightweight compared to metal materials, and can be formed by controlling the hot pressing parameters, thus also having the advantage of simple preparation process.

[0037] Another embodiment of this application provides an radome, which is made of a composite layer material obtained by the preparation method of any of the above embodiments. For example, the composite layer material obtained in the above embodiments can be cut to a predetermined size, the cut edges can be ground, and then bonded or welded to obtain the radome. When bonding, an adhesive with the same components as the adhesive layer can be used. After bonding, the radome can be placed in an oven and heated at 120-160°C for 1.5-2 hours. Since the radome is made of a composite layer material, it possesses both the material mechanical properties and wave transmission properties of the composite layer material.

[0038] The following detailed description of the composite layer material is provided using specific implementation methods.

[0039] Example 1 This embodiment provides a method for preparing a composite layer material, including the following steps. Step 1: In a hot press mold, a polypropylene prepreg tape layer 20, an adhesive layer 30, a polymethacrylamide foam core layer 40, an adhesive layer 30, and a polypropylene prepreg tape layer 20 are formed sequentially from bottom to top to form a preform.

[0040] Each polypropylene prepreg tape layer 20 has two stacked glass fiber reinforced polypropylene prepreg tapes 21. Viewed along the stacking direction of the preform, in each polypropylene prepreg tape layer 20, the lower polypropylene prepreg tape 21 is laid at 0°, and the upper polypropylene prepreg tape 21 is laid at 90°. The volume fraction of glass fiber in each polypropylene prepreg tape 21 is 45%, and the thickness of each polypropylene prepreg tape 21 is 0.15 mm. Each polypropylene prepreg tape 21 is made of PP unidirectional prepreg tape provided by Duoming Qingdao New Material Technology Co., Ltd. At this time, before hot pressing, the thickness of the polypropylene prepreg tape layer 20 is 0.3 mm.

[0041] Each adhesive layer 30 comprises nano-titanium dioxide (10nm anatase titanium dioxide, Ningbo Jiwei Nanomaterials Technology Co., Ltd.) and bisphenol A epoxy resin (Phoenix brand 618 E51 bisphenol A liquid epoxy resin, Hebei Gujia Technology Co., Ltd.). The amount of nano-titanium dioxide is 1% of the total weight of the adhesive layer components, with the remainder being bisphenol A epoxy resin. Before forming adhesive layer 30, the nano-titanium dioxide needs to be dispersed in the epoxy resin by stirring at a speed of 500-600 rpm for 30-60 minutes. In this embodiment, the stirring time is 60 minutes and the stirring speed is 600 rpm. This allows the adhesive layer components to be mixed before forming the preform. The mixing of the components of adhesive layer 30 in the following embodiments and comparative examples follows the same procedure and will not be described again. The thickness of each adhesive layer 30 is 0.3 mm.

[0042] The closed-cell rate of the polymethacrylimide foam core layer 40 is 95%-98%, and it is PMI foam core material (aerospace-grade high-temperature resistant series) purchased from Qingdao Jiachuang New Materials Co., Ltd., with a thickness of 15mm.

[0043] Step 2: Hot pressing preparation. The vacuum degree for hot pressing is -0.095 MPa. A three-stage heating method is used for hot pressing. The first stage heating method is to raise the hot pressing temperature to 70℃ and hold it for 15 minutes, with the heating rate controlled at 5-6℃ / min. The second stage heating method is to continue raising the hot pressing temperature to 130℃ and hold it for 15 minutes, with the heating rate controlled at 3-4℃ / min. The third stage heating method is to continue raising the hot pressing temperature to 140℃ and hold it for 25 minutes, with the heating rate controlled at 7-8℃ / min. During the first stage heating, the hot pressing pressure is 1.0 MPa. During the second stage heating, the hot pressing pressure is 0.7 MPa. During the third stage heating, the hot pressing pressure is 0.6 MPa, resulting in the hot-pressed body.

[0044] Step 3: Maintain the hot pressing pressure during the third stage of heating, i.e., maintain the hot pressing pressure at 0.6 MPa, stop heating, and allow the hot-pressed body to cool naturally to room temperature.

[0045] Step 4: Demolding to obtain the composite layer material.

[0046] Example 2 The difference from Example 1 is that in each adhesive layer 30, the amount of nano-titanium dioxide is 0.5% of the total weight of the adhesive layer components.

[0047] Example 3 The difference from Example 1 is that in each adhesive layer 30, the amount of nano-titanium dioxide is 2% of the total weight of the adhesive layer components.

[0048] Comparative Example 1 The difference from Example 1 is that in each adhesive layer 30, the amount of nano-titanium dioxide is 2.5% of the total weight of the adhesive layer components.

[0049] Comparative Example 2 The difference from Example 1 is that in each adhesive layer 30, the amount of nano-titanium dioxide is 0.4% of the total weight of the adhesive layer components.

[0050] Example 4 The difference from Example 1 is that in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 50%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 73°C and held for 13 minutes. In the second stage of heating, the hot pressing temperature is further raised to 127°C and held for 20 minutes, with the heating rate controlled at 2-3°C / min. In the third stage of heating, the hot pressing temperature is further raised to 160°C and held for 10 minutes, with the heating rate controlled at 8-9°C / min. In the first stage of heating, the hot pressing pressure is 0.9 MPa. In the second stage of heating, the hot pressing pressure is 0.8 MPa. In the third stage of heating, the hot pressing pressure is 0.5 MPa.

[0051] Example 5 The difference from Example 1 is that in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 60%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 90°C and held for 5 minutes. In the second stage of heating, the hot pressing temperature is further raised to 110°C and held for 25 minutes. In the third stage of heating, the hot pressing temperature is further raised to 143°C and held for 19 minutes. The heating rate is controlled at 9-10°C / min. In the first stage of heating, the hot pressing pressure is 0.9 MPa. In the second stage of heating, the hot pressing pressure is 0.8 MPa. In the third stage of heating, the hot pressing pressure is 0.5 MPa.

[0052] Example 6 The difference from Example 1 is that, in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 53%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 74°C and held for 15 minutes. In the second stage of heating, the hot pressing temperature is further raised to 113°C and held for 23 minutes, with the heating rate controlled at 2-3°C / min. In the third stage of heating, the hot pressing temperature is further raised to 154°C and held for 11 minutes, with the heating rate controlled at 8-9°C / min. In the first stage of heating, the hot pressing pressure is 0.9 MPa. In the second stage of heating, the hot pressing pressure is 0.8 MPa. In the third stage of heating, the hot pressing pressure is 0.5 MPa.

[0053] Example 7 The difference from Example 1 is that in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 54%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 75°C and held for 11 minutes. In the second stage of heating, the hot pressing temperature is further raised to 120°C and held for 17 minutes, with the heating rate controlled at 2-3°C / min. In the third stage of heating, the hot pressing temperature is further raised to 155°C and held for 20 minutes, with the heating rate controlled at 9-10°C / min. In the first stage of heating, the hot pressing pressure is 0.9 MPa, and in the third stage of heating, the hot pressing pressure is 0.5 MPa.

[0054] Example 8 The difference from Example 1 is that in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 58%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 85°C and held for 9 minutes. In the second stage of heating, the hot pressing temperature is further raised to 115°C and held for 19 minutes. In the third stage of heating, the hot pressing temperature is further raised to 145°C and held for 23 minutes. The heating rate is controlled at 9-10°C / min. In the second stage of heating, the hot pressing pressure is 0.8 MPa.

[0055] Comparative Example 3 The difference from Example 1 is that in each polypropylene prepreg tape 21, the volume fraction of glass fiber is 62%. During hot pressing, in the first stage of heating, the hot pressing temperature is raised to 90°C and held for 5 minutes. In the second stage of heating, the hot pressing temperature is further raised to 110°C and held for 25 minutes. In the third stage of heating, the hot pressing temperature is further raised to 143°C. The heating rate is controlled at 9-10°C / min. In the first stage of heating, the hot pressing pressure is 0.9 MPa. In the second stage of heating, the hot pressing pressure is 0.8 MPa. In the third stage of heating, the hot pressing pressure is 0.5 MPa.

[0056] Comparative Example 4 The difference from Example 1 is that during hot pressing, the hot pressing temperature is raised to 68°C in the first stage of heating, further raised to 131°C in the second stage of heating, and further raised to 138°C in the third stage of heating.

[0057] Comparative Example 5 The difference from Example 1 is that during hot pressing, the hot pressing temperature is raised to 91°C in the first stage of heating, further raised to 108°C in the second stage of heating, and further raised to 140°C in the third stage of heating.

[0058] Example 9 The difference from Example 1 is that each adhesive layer 30 has a thickness of 0.1 mm. The components of adhesive layer 30 also include polyether-modified organopolysiloxane (product number xyh001, brand name Xinyuhong, Hubei Xinyuhong Biomedical Technology Co., Ltd.), ethylene propylene non-conjugated diene terpolymer grafted maleic anhydride (EPDM grafted maleic anhydride, brand name W1P-2, Keaisi), polypropylene grafted maleic anhydride (brand name B1, Keaisi), and organic solvent (toluene, Sigma-Aldrich). The amount of polyether-modified organopolysiloxane is 2% of the total weight of the adhesive layer components, the amount of ethylene propylene non-conjugated diene terpolymer grafted maleic anhydride is 2% of the total weight of the adhesive layer components, the amount of polypropylene grafted maleic anhydride is 5% of the total weight of the adhesive layer components, the amount of organic solvent is 6% of the total weight of the adhesive layer components, and the balance is epoxy resin. The weight ratio of ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride to polypropylene grafted with maleic anhydride is 1:2.5.

[0059] Example 10 The difference from Example 2 is that the components of adhesive layer 30 also include polyether-modified organopolysiloxane (TY-H26, Greenlink Jining Chemical Technology Co., Ltd.), ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride (EPDM grafted maleic anhydride, brand name W1P-2, Coex), polypropylene grafted maleic anhydride (brand name B1, Coex), and organic solvent (toluene, Sigma-Aldrich). The amount of polyether-modified organopolysiloxane is 0.5% of the total weight of the adhesive layer components, the amount of ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride is 4% of the total weight of the adhesive layer components, the amount of polypropylene grafted maleic anhydride is 3% of the total weight of the adhesive layer components, the amount of organic solvent is 8% of the total weight of the adhesive layer components, and the balance is epoxy resin. The weight ratio of ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride to polypropylene grafted maleic anhydride is 1:0.75.

[0060] Example 11 The difference from Example 3 is that the components of adhesive layer 30 also include polyether-modified organopolysiloxane (TY-H26, Greenlink Jining Chemical Technology Co., Ltd.), ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride (EPDM grafted maleic anhydride, brand name W1P-2, Coex), polypropylene grafted maleic anhydride (brand name B1, Coex), and organic solvent (toluene, Sigma-Aldrich). The amount of polyether-modified organopolysiloxane is 3% of the total weight of the adhesive layer components, the amount of ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride is 5% of the total weight of the adhesive layer components, the amount of polypropylene grafted maleic anhydride is 7% of the total weight of the adhesive layer components, the amount of organic solvent is 10% of the total weight of the adhesive layer components, and the balance is epoxy resin. The weight ratio of ethylene-propylene non-conjugated diene terpolymer grafted maleic anhydride to polypropylene grafted maleic anhydride is 1:1.2.

[0061] Example 12 The difference from Example 9 is that the amount of polyether-modified organopolysiloxane is 1% of the total weight of the adhesive layer components, the amount of ethylene propylene non-conjugated diene terpolymer grafted with maleic anhydride is 3% of the total weight of the adhesive layer components, the amount of polypropylene grafted with maleic anhydride is 4.5% of the total weight of the adhesive layer components, the amount of organic solvent is 8% of the total weight of the adhesive layer components, and the weight ratio of ethylene propylene non-conjugated diene terpolymer grafted with maleic anhydride to polypropylene grafted with maleic anhydride is 1:1.5.

[0062] Example 13 The difference from Example 9 is that the amount of maleic anhydride grafted onto the ethylene-propylene non-conjugated diene terpolymer is 3% of the total weight of the adhesive layer components, the amount of maleic anhydride grafted onto the polypropylene is 3% of the total weight of the adhesive layer components, the amount of the organic solvent is 5% of the total weight of the adhesive layer components, and the weight ratio of maleic anhydride grafted onto the ethylene-propylene non-conjugated diene terpolymer to maleic anhydride grafted onto the polypropylene is 1:1.

[0063] Example 14 The difference from Example 9 is that the epoxy resin is composed of silicone-modified epoxy resin (TY-H26, Greenlink Jining Chemical Technology Co., Ltd.) and bisphenol A type epoxy resin, with a weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin of 1:35.

[0064] Example 15 The difference from Example 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:38.

[0065] Example 16 The difference from Example 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:40.

[0066] Example 17 The difference from Example 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:43.

[0067] Example 18 The difference from Implementation 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:45.

[0068] Example 19 The difference from Implementation 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:50.

[0069] Example 20 The difference from Implementation 14 is that the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:34.

[0070] Comparative Example 6 The difference from Example 9 is that the components of adhesive layer 30 do not include polyether-modified organopolysiloxane.

[0071] Comparative Example 7 The difference from Example 9 is that the components of adhesive layer 30 do not include ethylene propylene non-conjugated diene terpolymer grafted maleic anhydride.

[0072] Example 21 The difference from Example 1 is that each polypropylene prepreg tape layer 20 has four stacked layers of glass fiber reinforced polypropylene prepreg tape 21. Viewed along the stacking direction of the prepreg body, in each polypropylene prepreg tape layer 20, the bottommost polypropylene prepreg tape 21 is laid at 0°, the next layer is laid at 90°, the next still layer at +45°, and the topmost layer at -45°. The thickness of each polypropylene prepreg tape layer 20 is 0.6 mm. The thickness of the polymethacrylimide foam core layer 40 is 10 mm.

[0073] Comparative Example 8 The difference from Example 1 is that during the hot pressing preparation, the temperature is raised to 140°C and held for 25 minutes, with a heating rate of 7-8°C / min and a hot pressing pressure of 0.8 MPa.

[0074] Comparative Example 9 The difference from Example 1 is that the same hot pressing pressure of 0.8 MPa is used for the first, second and third stages of heating.

[0075] Comparative Example 10 The difference from Example 1 is that in step three, the operation of maintaining the hot-pressing pressure is cancelled, and the pressure is released directly after the hot-pressed body is obtained.

[0076] The performance data of Examples 1-8 and Comparative Examples 1-3 are summarized in Table 1.

[0077] Table 1 summarizes the test data for Examples 1-8 and Comparative Examples 1-3.

[0078]

[0079] The performance data of Examples 9-17 and Comparative Examples 4-5 are summarized in Table 2.

[0080] Table 2 shows the test data for Examples 9-17 and Comparative Examples 4-5.

[0081]

[0082] The performance data of Examples 18-21 and Comparative Examples 6-10 are summarized in Table 3.

[0083] Table 3 shows the test data for Examples 18-21 and Comparative Examples 6-10.

[0084]

[0085] X-band transmittance conforms to GJB 7954-2012 standard, with a frequency range of 8-12 GHz.

[0086] The experimental standard for the low-temperature falling ball impact test is based on the international standard ISO 6603-2, and the test conditions are: -40℃ for 8 hours.

[0087] The flexural modulus of elasticity is tested in accordance with the ISO 14125 international standard.

[0088] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a composite layer material, characterized in that, Includes the following steps: In a hot press mold, a prepreg tape layer, an adhesive layer, a polymethacrylamide foam core layer, another adhesive layer, and a polymethacrylamide tape layer are formed sequentially from bottom to top to form a preform. The closed-cell rate of the polymethacrylamide foam core layer is greater than or equal to 95%. The adhesive layer comprises epoxy resin and nano-titanium dioxide, with the amount of nano-titanium dioxide being 0.5%-2% of the total weight of the adhesive layer components. The polymethacrylamide tape layer is formed by laying glass fiber reinforced polymethacrylamide tape, in which the volume fraction of glass fiber is 45%-60%. The pre-pressed body is hot-pressed with a vacuum degree ≤ -0.095MPa. The hot-pressing process employs a three-stage heating method: the first stage involves raising the temperature to 70-90℃ and holding it for 5-15 minutes; the second stage involves raising the temperature further to 110-130℃ and holding it for 15-25 minutes; and the third stage involves raising the temperature further to 140-160℃ and holding it for 10-25 minutes. During the first stage of heating, the hot-pressing pressure is 0.9-1.0 MPa; during the second stage, the pressure is 0.7-0.8 MPa; and during the third stage, the pressure is 0.5-0.6 MPa, resulting in the hot-pressed body. Maintain the hot-pressing pressure during the third stage of heating, then stop heating and allow the hot-pressed body to cool naturally to room temperature; Demolding yields the composite layer material.

2. The preparation method according to claim 1, characterized in that, During the second stage of heating, the hot-pressing temperature is further increased to 110-120℃.

3. The preparation method according to claim 1, characterized in that, The adhesive layer also includes polyether-modified organopolysiloxane, ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride, polypropylene grafted with maleic anhydride, and organic solvent. The amount of polyether-modified organopolysiloxane is 0.5%-3% of the total weight of the adhesive layer components, the amount of ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride is 2%-5% of the total weight of the adhesive layer components, the amount of polypropylene grafted with maleic anhydride is 3%-7% of the total weight of the adhesive layer components, the amount of organic solvent is 5%-10% of the total weight of the adhesive layer components, and the balance is the epoxy resin.

4. The preparation method according to claim 3, characterized in that, The epoxy resin is composed of silicone-modified epoxy resin and bisphenol A type epoxy resin, and the weight ratio of silicone-modified epoxy resin to bisphenol A type epoxy resin is 1:(35-45).

5. The preparation method according to claim 4, characterized in that, The weight ratio of the organosilicon-modified epoxy resin to the bisphenol A type epoxy resin is 1:(40-45).

6. The preparation method according to any one of claims 3 to 5, characterized in that, The weight ratio of the ethylene-propylene non-conjugated diene terpolymer grafted with maleic anhydride to the polypropylene grafted with maleic anhydride is 1:(1-1.5).

7. The preparation method according to claim 6, characterized in that, During the first stage of heating, the heating rate is 5-6℃ / min; during the second stage of heating, the heating rate is 2-4℃ / min; and during the third stage of heating, the heating rate is 7-10℃ / min.

8. The preparation method according to claim 1, characterized in that, The polypropylene prepreg tape layer has at least two stacked layers of polypropylene prepreg tape, and the laying direction of each layer of polypropylene prepreg tape is one of 0°, 90°, and ±45°, and the laying direction of the polypropylene prepreg tape of different layers is different.

9. The preparation method according to claim 1, characterized in that, Before hot pressing, the thickness of the polypropylene prepreg tape layer is 0.3-0.6 mm, the thickness of the polymethacrylimide foam core layer is 10-15 mm, and the thickness of the adhesive layer is 0.1-0.3 mm.

10. A radome, characterized in that, The radome is made of a composite material layer obtained by the preparation method according to any one of claims 1 to 9.